2019
DOI: 10.1091/mbc.e18-12-0770
|View full text |Cite
|
Sign up to set email alerts
|

Stretching magnitude–dependent inactivation of AKT by ROS led to enhanced p53 mitochondrial translocation and myoblast apoptosis

Abstract: Previously, we had shown that high magnitude stretch (HMS), rather than low magnitude stretch (LMS), induced significant apoptosis of skeletal muscle C2C12 myoblasts. However, the molecular mechanism remains obscure. In this study, we found that p53 protein accumulated in the nucleus of LMS-loaded cells, whereas it translocated into mitochondria of HMS-loaded cells. Knocking down endogenous p53 by shRNA abrogated HMS-induced apoptosis. Furthermore, we demonstrated that overaccumulation of reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The myostatin gene activates Smad2 signaling and inhibits Akt activation, thereby altering the expression of multiple genes involved in the regulation of protein degradation and increasing skeletal muscle apoptosis [ 9 , 72 , 73 ]. Previous studies on ROS-related factors inducing myoblast apoptosis have shown that the p53 and Akt pathways are involved in cell apoptosis and ROS accumulation [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The myostatin gene activates Smad2 signaling and inhibits Akt activation, thereby altering the expression of multiple genes involved in the regulation of protein degradation and increasing skeletal muscle apoptosis [ 9 , 72 , 73 ]. Previous studies on ROS-related factors inducing myoblast apoptosis have shown that the p53 and Akt pathways are involved in cell apoptosis and ROS accumulation [ 74 , 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mitochondrion was another important organelle involving in stretching-induced myoblast death, with mitochondrial maker protein apoptosis-inducing factor (AIF) level being elevated during mechanical stretch [84]. Furthermore, we found a stretching magnitude-dependent increment of reactive oxygen species (ROS) in C2C12 myoblasts, which activated two pathways that contribute to myoblast death: JNK and p53 [85,86]. When ROS was inhibited, stretch-activated JNK was also attenuated; inhibition of both ROS and JNK could alleviate myoblast apoptosis under stretching stimuli [85].…”
Section: Molecular Mechanisms Of Stretch-induced Myoblast Deathmentioning
confidence: 79%
“…When ROS was inhibited, stretch-activated JNK was also attenuated; inhibition of both ROS and JNK could alleviate myoblast apoptosis under stretching stimuli [85]. Furthermore, ROS-induced p53 mitochondrial translocation only occurred when ROS was overaccumulated by stretching stimuli, which was a critical event leading to myoblast apoptosis, possibly depending upon classical mitochondrial apoptotic pathways [86].…”
Section: Molecular Mechanisms Of Stretch-induced Myoblast Deathmentioning
confidence: 97%
See 1 more Smart Citation
“…Cyclic mechanical stretch is a known inducer of the up-regulated level of reactive oxygen species (ROS) [4,5]. ROS, as intracellular signaling molecules, can be essential for regulation of cell physiological functions, while excessive accumulation of ROS can disrupt physiological functions and cause numerous pathophysiological processes [6].…”
Section: Introductionmentioning
confidence: 99%